The Arabidopsis AAC Proteins CIL and CIA2 Are Sub-functionalized Paralogs Involved in Chloroplast Development - Li, Mingjiu; Ruwe, Hannes; Melzer, Michael; Junker, Astrid; Hensel, Goetz; Tschiersch, Henning; Schwenkert, Serena; Chamas, Sindy; Schmitz-Linneweber, Christian; Börner, Thomas; Stein, Nils (Frontiers in Plant Science, 2021)
The Arabidopsis gene Chloroplast Import Apparatus 2 (CIA2) encodes a transcription factor that positively affects the activity of nuclear genes for chloroplast ribosomal proteins and chloroplast protein import machineries. CIA2-like (CIL) is the paralogous gene of CIA2. We generated a cil mutant by site-directed mutagenesis and compared it with cia2 and cia2cil double mutant. Phenotype of the cil mutant did not differ from the wild type under our growth conditions, except faster growth and earlier time to flowering. Compared to cia2, the cia2cil mutant showed more impaired chloroplast functions and reduced amounts of plastid ribosomal RNAs. In silico analyses predict for CIA2 and CIL a C-terminal CCT domain and an N-terminal chloroplast transit peptide (cTP). Chloroplast (and potentially nuclear) localization was previously shown for HvCMF3 and HvCMF7, the homologs of CIA2 and CIL in barley. We observed nuclear localization of CIL after transient expression in Arabidopsis protoplasts. Surprisingly, transformation of cia2 with HvCMF3, HvCMF7 or with a truncated CIA2 lacking the predicted cTP could partially rescue the pale-green phenotype of cia2. These data are discussed with respect to potentially overlapping functions between CIA2, CIL and their barley homologs and to the function of the putative cTPs of CIA2 and CIL.